Una propuesta para la localización de áreas de servicio y descanso adaptadas al transporte de mercancías peligrosas mediante un modelo de optimización; aplicación al territorio espa\~nol - María Dolor Caro Vela; Concepción Paralera Morales (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2011)
– This paper analyzes the importance of having a network of stations adapted to vehicles carrying dangerous goods. In the rst place, it is studied the current demand which is offered by the existing parking areas, and in the second place, it is explained a maximum coverage location model in order to study the location of areas that meet the drivers' demand of rest to a greater extent complying with legal and safety regulations. The model is applied into Spanish territory with the help of geographic information systems (GIS).
Keywords: C61; 330; maximal covering location model; transport of dangerous goods; geographic information system